VIOLENCE IN THE CITY OF SÃO PAULO IN THE XX CENTURY. - Da Silva, Olga Maria Panhoca; Panhoca, Luiz (Revista Salusvita, 2005)
The article examines the incidence of violence in Sao Paulo City during the 20th century in Brazil. Violence in the city is determined through the use of legal medicine and necropsy reports. Morbidity analysis grouped according to the type of violence including interpersonal aggression and legal intervention.